Pengaruh Perendaman Resin Akrilik Dalam Ekstrak Daun Turi (Sesbania grandiflora) Terhadap Candida albicans - Joshua, Brighton; Yuliarsi, Yayuk (Fakultas Kedokteran Gigi Universitas Trisakti, 2025)
One of the materials that can be used as an alternative denture cleaner is turi leaf (Sesbania grandiflora). The content of secondary metabolites in turi leaf plays a major role in inhibiting the growth of Candida albicans fungi. Unclean dentures can result in the formation of C. albicans from the accumulation of food debris. The microporosity of heat cured acrylic resin causes C.albicans to stick more easily. Therefore, dentures must be cleaned chemically or immersing it in a cleaning solution for a certain duration. Objective: To determine the effect of immersion duration of heat cured acrylic resin in turi leaf extract (Sesbania grandiflora) on the growth of C. albicans. Research Methods: This study used 40 acrylic resin plates which were divided into 8 groups of turi leaf extract immersion of 25% concentration with a duration of 6 hours and 8 hours, 50% concentration with a duration of 6 hours and 8 hours, 2% chlorhexidine gluconate (positive control), and Saboraud Dextrose Broth (negative control), then rinsed and vortexed in PBS and counted C. albicans colonies on agar medium that had been scraped with the PBS solution. Result: In a study on C. albicans, the data showed a normal distribution (p>0.05). A One-Way ANOVA test indicated significant differences (p